1996
DOI: 10.1034/j.1600-0501.1996.070305.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between radiographic, clinical and mobility parameters after loading of oral implants with fixed partial dentures. A 2‐year longitudinal study.

Abstract: The aim of present study was to correlate the changes in the peri-implant tissues occurring after functional loading of non-submerged titanium implants and assessed by radiographic, clinical and mobility measurements. 11 patients with distal extension situations received 18 implants of the ITI Dental Implant System. After a healing period of 3 months, the suprastructures were fabricated and seated 5 months post-surgically. For the assessment of peri-implant bone changes, standardized vertical bitewing radiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 0 publications
3
57
1
1
Order By: Relevance
“…The two year longitudinal study of Brägger et al [13] confirmed that the measurements of probing attachment level (PAT) along with radiographic parameters were good predictors of peri-implant bone level. The use of modified periodontal indices was suggested later [23,32].…”
Section: Other Predictors Of Bone Loss and Implant Successmentioning
confidence: 65%
See 4 more Smart Citations
“…The two year longitudinal study of Brägger et al [13] confirmed that the measurements of probing attachment level (PAT) along with radiographic parameters were good predictors of peri-implant bone level. The use of modified periodontal indices was suggested later [23,32].…”
Section: Other Predictors Of Bone Loss and Implant Successmentioning
confidence: 65%
“…The effects of the projection and the beam angle on the interpretation of non standardized films were reported by many authors [13][14][15].…”
Section: Radiographic Methodologymentioning
confidence: 99%
See 3 more Smart Citations